2007
DOI: 10.5012/bkcs.2007.28.5.725
|View full text |Cite
|
Sign up to set email alerts
|

Density Functional Theory Study of Acetonitrile -Water Clusters: Structures and Infrared Frequency Shifts

Abstract: We present calculations for the acetonitrile -water clusters to examine the nature of interactions in the mixed clusters. We calculate conformers of various composition, either of σ-type (-OH and -CN binding linearly) or π-type (-OH and -CN interacting perpendicularly) structures for the acetonitrile -water clusters. We predict that the IR frequency of the proton-accepting C≡N stretching mode red-shifts in the σ-type clusters and blueshifts in π-type conformers, whereas the proton-donating -OH stretching frequ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
5
0

Year Published

2009
2009
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 27 publications
1
5
0
Order By: Relevance
“…Most evident in the 130 K x (CH 3 CN) = 0.8 binary ice shown in Figure , a pronounced satellite peak is observed toward the red edge at 2245 cm –1 . This peak likely indicates that a portion of the CH 3 CN component interacts with H 2 O via side-directed π-type hydrogen bonding, as a similar satellite peak is computed for the (H 2 O) 2 –(CH 3 CN) 2 cluster . Other studies have assigned the CH 3 CN···HOH complex by way of a red-shifted CN satellite band arising from strong dipole–dipole interactions (Figure S-6e).…”
Section: Resultssupporting
confidence: 62%
“…Most evident in the 130 K x (CH 3 CN) = 0.8 binary ice shown in Figure , a pronounced satellite peak is observed toward the red edge at 2245 cm –1 . This peak likely indicates that a portion of the CH 3 CN component interacts with H 2 O via side-directed π-type hydrogen bonding, as a similar satellite peak is computed for the (H 2 O) 2 –(CH 3 CN) 2 cluster . Other studies have assigned the CH 3 CN···HOH complex by way of a red-shifted CN satellite band arising from strong dipole–dipole interactions (Figure S-6e).…”
Section: Resultssupporting
confidence: 62%
“…They studied acetonitrile complex with phenol. Like previous works [14,15], they also concentrated on C N stretching mode in both  type (OH and CN linear interaction) and  (OH and CN perpendicular interaction) hydrogen bonds.…”
Section: Computational Study Of Hydrogen Bonding In Ch 3 Cn•••h-x (X=oh F CL Nh 2 ) Complexesmentioning
confidence: 79%
“…So far there are few reports regarding computational studies of acetonitrile complex [14][15][16][17][18][19][20][21]. In almost all studies acetonitrilewater complexes have been reported.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The first peak belongs to the formation of H-bonds between acetonitrile and water molecules (N···H water or O···H ACN ). A presence of such hydrogen bonded complexes was reported from density functional theory based calculations, although exact structural details were absent in the literature . The other total distribution functions involving H···O (or N) interactions showed the presence of multiple small clusters in the binary mixtures of different concentrations of ACN.…”
Section: Resultsmentioning
confidence: 94%